Abdomen-still a pandora’s box - Devi, L. Thulasi; Kalam, Adil Abdul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
An interesting case of young lady who had undergone obstetric hysterectomy during delivery with left ovary in situ. She was taken up for laparoscopic oopherectomy at a later date for a large ovarian mass on left side which was removed. She presented to us with recurrence of pelvic mass. Preoperatively we were reminded of the adage and popular saying.” Abdomen-still a pandora’s box.” This article attempts to present the importance of truthful case notes in failed surgeries and effective communication to the patient to prevent clinical and surgical misadventures and dilemmas.